Model Collaboration: University Library System and Rehabilitation Research Team to Advance Telepractice Knowledge - Timothy S. Deliyannides; Vanessa E. Gabler (International Journal of Telerehabilitation)
This Publisher’s Report describes the collaboration between a university library system’s scholarly communication and publishing office and a federally funded research team, the Rehabilitation Engineering Research Center (RERC) on Telerehabilitation. This novel interdisciplinary collaboration engages librarians, information technologists, publishing professionals, clinicians, policy experts, and engineers and has produced a new Open Access journal, International Journal of Telerehabilitation, and a developing, interactive web-based product dedicated to disseminating information about telerehabilitation.  Readership statistics are presented for March 1, 2011 - February 29, 2012.